Pengaruh Daya Tarik Objek Wisata terhadap Minat Berkunjung di Gunung Geulis Camp Area Bogor - Sutiyadi, Muhammad; Djunaid, Ika Suryono (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Tourist Attraction is a support for Mount Geulis Camp Area Bogor which is very persuasive in making visitors interested and visiting. Tourist Attractions have differences starting with Attraction, Accessibility, Amenities and Ancillary Service. This study aims to determine the effect of tourist attraction on visiting intentions and strengthen existing theories. This study used a 100-response sample, and a questionnaire and a Likert scale were used for data collection. Validity, reliability, normality, and heteroscedasticity tests were then used in this study. The information checking strategy used in this review is the basic straight relapse check technique, then using speculation tests, namely the specific t test and f test, the coefficient of determination test (R2). Based on the results of the T test, Attraction Amenities, Ancillary it can be concluded that acceptance has a Partial Influence on Interest in Visiting the Mount Geulis Camp Area Bogor, while Accessibility has no Partial Influence on Interest in Visiting the Mount Geulis Camp Area Bogor. and the results of the f test show that the variable Tourist Attractiveness and indicators affect the intention to visit simultaneously. Then the results of the test for the coefficient of determination can show that the value of r square is 29.9%, and it implies that there is an influence relationship between Tourist Attractiveness on visiting interest. then at that time, while the remaining 70.1% was influenced by various factors which will not be reviewed in this review. Keywords: tourist attraction, mount Geulis camp Bogor area, interest in visiting.